Nitrate removal using natural clays modified by acid thermoactivation - Mena-Durán, C.J.; Sun-Kou, M.R.; López, T.; Azamar-Barrios, J.A.; Aguilar, D.H.; Domínguez, M.I.; Odriozola, J.A.; Quintana-Owen, P. (Elsevier, 2007)
Groundwater pollution by nitrates is a widespread problem in many locations in the world. The underground aquatic mantle of the Peninsula of Yucatan is highly vulnerable due to its karstic nature. Adsorption methods are a good choice for nitrate elimination. In this work, a natural calcium bentonite was modified by acid thermoactivation with HCl and H2SO4, and tested as a media for nitrate removal in an aqueous solution. The nitrate concentration in the solution was measured by FT-IR, using the Lambert–Beer law. Clay characterization was carried out by X-ray diffraction and FT-IR spectroscopy; surface area was measured by the BET method.
Keywords: Groundwater—Pollution; Bentonite; https://purl.org/pe-repo/ocde/ford#1.05.03